Ion-selective membrane modified microfluidic paper-based solution sampling substrates for potentiometric heavy metal detection - Silva, Rochelle (2022)
Paper-based microfluidic solution sampling is a viable option for potentiometric sensors to be used for the determination of analytes in samples with high solid-to-liquid ratios. Unfortunately, heavy metal sensitive electrodes cannot be easily integrated with paper-based solution sampling as heavy metals have strong physicochemical adsorption affinity towards paper substrates. In this work, paper substrates were modified with an ion-selective membrane (ISM) cocktail (used for the preparation of Pb2+-ion-selective electrodes (ISEs)) and coupled with model heavy metal Pb2+-ISEs. It was found that the super-Nernstian response of Pb2+-ISEs was eliminated when 10 to 50 mg ml-1 of the ISM cocktail was used for the modification of paper substrates. The modification of the paper substrates by Pb2+-ISM allowed the elimination of adsorption sites. In addition, it resulted in an improvement of sensor performance in terms of their detection limits to be similar to those for conditioned electrodes in standard beaker-based measurements. It is believed that the elimination of super-Nernstian response of the electrodes and improving the potentiometric responses and detection limits of ISEs were attributed to the compatibility improvement of the paper substrates and Pb2+-ISEs to the same type of ISM.